Administration of resources and their contribution to national defense: a vision to the 2021 bicentenary plan - Diaz Guevara, Hernan (2019)
The Peruvian Air Force, within its real estate patrimony, owns real estate that currently doesn´t have ownership that determines the right of ownership, reason for which they cannot be registered in the National Superintendence of Public Registries. In this sense, the purpose of this research was to analyze the factors that limit the achievement of the objectives with respect to the third strategic axis of the Bicentennial Plan Peru 2021, in the administration and management of the resources available to the Peruvian Air Force. By means of the qualitative methodology, the technical support was elaborated to carry out the physical - legal cleaning and to give a better use to the real estate patrimony, in addition the guidelines of the hermeneutic investigation were followed, since its individual character allowed the interaction with the reality, by means of the analysis of documents and cases with which it was possible to categorize the phenomenon in study. Finally, it was concluded that there are factors that limit the achievement of the objectives with respect to the third strategic axis of the Bicentennial Plan Peru 2021, in the administration and management of the resources of the Peruvian Air Force.